In Silico Testing on the Activity of Quercetin in the Skin of Onion Allium Cepa L as A Natural Antihypertensive Compound - Andi Ariyandy; Nindrahayu; Ami Febriza; Andi Irwan Muluk; Sulfahri (International Journal of Applied Biology, 2022)
This study aims to determine the bioactivity of the compound quercetin in the peel of Allium cepa L as a natural antihypertensive compound. The chemical structure of the quercetin compound found in Allium cepa L peel was taken from the literature. The target protein used was Angiotensin-Converting Enzyme (ACE), while the control compound was lisinopril. Water molecules were removed using PyMol v2.5.2 Software. Docking between the target protein and the compound was carried out using PyRx-Python Prescription 0.8 Software. The results showed that the quercetin compound had more significant potential as an antihypertensive compared to lisinopril as a control compound. The affinity ratio of the Angiotensin-converting enzyme with quercetin is -8.1, while the affinity value of the Angiotensin-converting enzyme with lisinopril is -7.1.